Revealing the impacts of human activity on the aquatic environment of the Pearl River Estuary, South China, based on sedimentary nutrient records. (20th January 2023) - Li, Rui; Liang, Zuobing; Hou, Lei; Zhang, Di; Wu, Qirui; Chen, Jianyao; Gao, Lei
Abstract: Elucidating environmental evolution and its influencing factors in estuarine areas is essential to coastal and marine ecological management. In this study, the spatiotemporal distributions of organic carbon (OC), total nitrogen (TN), total phosphorus (including geochemical speciation), δ 13 C and nutrient ratios in sediments were explored to interpret changes in the aquatic environment of the Pearl River Estuary (PRE), and their sources in various periods were identified. Nutrients carried by surface runoff accumulated abundantly in the sediments of the northern and western shoals. Two dated sediment cores indicated a close relationship between environmental evolution in the PRE and the socioeconomic development of the Pearl River Delta (PRD). Rapid urbanization and population explosion in the PRD transformed the PRE from the pre-1970 low-impact state to a eutrophic state, which lasted until the end of the 1990s. After 2000, improvement of sewage treatment systems and environmental governance policies promoted the restoration of water quality, although inorganic nitrogen remained high in the coastal waters. Based on the threshold of sedimentary TN/OP ratio (5.60) of red-tide occurrence, the eastern shoal of the PRE exhibited high potential for red tides. Agricultural activities along the western coast lowered sedimentary OC/TN ratios (6.51 ± 1.54) near the river's outlets. The sedimentary δ 13 C of organic matter (OM) in surface and subsurface sediments fell into the range of soil OM (−25.46 ± 0.82‰), suggesting an expanding influence of eroded soil from land reclamation on Longxue Island. This research revealed the intense influence of human activities on the aquatic-environmental evolution and provides scientific basis for environmental restoration of the PRE in the future. Graphical abstract: Image 1 Highlights: Spatial-temporal distribution of sediment nutrients was related to human activities. Eutrophication of estuarine water environment began to intensify after the 1970s. High-efficiency sewage treatment promoted the restoration of aquatic environment. Land reclamation contributed prominently to sediment OC in the Pearl River estuary.